Strongly almost summable difference sequences of order m defined by a modulus - Et, M (Akademiai Kiado, 2003)
The purpose of this paper is to introduce the space of sequences that are Delta(tau)-strongly almost summable with respect to a modulus function. We give some relations related to these sequence spaces. We also show that the space (s) over cap(Delta(tau)) of Delta(tau)-almost statistically convergen t sequences may be represented as a [(c) over cap, f] (Delta(tau)) space.
Keywords: Spaces; Convergence